SUSTAINING COMPETITIVE ADVANTAGE - Mohd Noor, Nurulainy (2007)
E.ON entrepreneurship has long been recognised as a potentially viable means for promoting and sustaining corporate competitiveness. Scholl Hammer (1982), Miller (1983), Guth and Ginsberg (1990), Nam and Slevin (1993), and Lumpkin and Dess (1996), for example, have all noted that corporate entrepreneurship can be used to improve competitive positioning and transform corporations, their markets, and industries as opportunities for clue-creating innovation are developed and exploited. However, only in recent years has much empirical evidence been provided which justifies the conventional wisdom that corporate entrepreneurship leads to superior firm performance. Perhaps the best evidence of a strong corporate entrepreneurship-performance relationship is provided in a study by Zahra and Covin (1995). Their study examined the longitudinal impact of corporate entrepreneurship on a financial performance index composed of both growth and profitability indicators. Using data collected from three separate samples and a total of 108 firms, Zahra and Covin (1995) identified a positive and strengthening linkage between corporate entrepreneurial behaviour and subsequent financial performance. In the present global business environment, firms must develop a competitive strategy that determines the position of the firm with respect to other firms in the industry. A structural analysis, which is fundamental in developing a competitive strategy, relates the firm to its environment. The firm must determine what its critical strengths and weaknesses are, and in what areas a change in strategy will yield the greatest benefit. It may be mentioned that the competitive advantage can be achieved if the organisation is able to develop an overall cost leadership without ignoring quality and service. The competitive advantage of being the low cost producer of a product is that, even in strongly competitive markets, the firm will earn above average returns. Those returns can be reinvested into the firm and used to purchase new equipment and facilities that will help perpetuate the firm's low cost position (Zahra, 1991, pp. 259-285). In order to become the low cost producer, E.ON must examine their internal processes. Through the implementation of smart metering, E.ON may provide services by performing a set of activities that create value. These activities form a value chain. A firm is profitable if the outcome of the value chain provides a service or product that can be sold for more than the producer spent in product creation and delivery. The firm must examine how to increase the value of the activities in the value chain. The value chain must be analysed as a system, from supplier to firm to distribution channel. There are several methods that have been developed for adding value to the value chain. One method that is currently popular is activity-based cost management (AM). AM unites activity-based costing (ABC) and activity-based management (ABM) techniques into a valuable system for managerial decision-making. In E.ON, AM started as an accounting method to deal with the phenomenon of misallocated overhead costs. This method has become a management tool, a corporate philosophy, which can identify inadequacies and waste in product costs, business processes, and management practices. It should not be viewed as the exclusive property of any particular department or group such as finance or accounting, but should be integrated into the corporate strategy and culture. Techniques such as AM must be used in the present competitive global business environment to create and maintain an overall cost leadership. Managers and employees must understand the basic principles of AM so that it can be used to its fullest potential. Commitment by management is necessary to the success of AM program. This commitment needs to be incorporated into the business culture and employee population through the use of training programs, team building efforts, and recognition of each small success (Zahra, 1991, pp. 259-285). The AM system can be linked with continuous improvement and planning tools such as total quality management (TQM), statistical quality control, business process analysis and value engineering programs. Activities performed during the work process become the key element in determining the value of the process. AM can be used to determine competitive competencies, product and customer profitability, or the value of a work process. AM is a system capable of tracing costs to products, services, processes, and customers. The common denominator in every business is the activities performed to produce a product or service. The AM method is based on the principle that activities consume resources and resources cost money. Therefore, if one can trace the activities to the product or service the true cost is determined. The focus of AM is to provide management with cost and operational information necessary to make strategic decisions concerning their competitive position. This system allows managers to identify products and services that are money makers or money losers (Armstrong, 2001, pp.99-121). This thesis is an attempt to discuss the challenge of sustaining competitive advantage in a detailed and comprehensive way using authentic sources including books, journals, magazines, reliable websites and interviews. This is then applied to the case of E.ON.